2009
DOI: 10.4007/annals.2009.170.205
|View full text |Cite
|
Sign up to set email alerts
|

Inverse spectral problem for analytic domains, II: ℤ2-symmetric domains

Abstract: This paper develops and implements a new algorithm for calculating wave trace invariants of a bounded plane domain around a periodic billiard orbit. The algorithm is based on a new expression for the localized wave trace as a special multiple oscillatory integral over the boundary, and on a Feynman diagrammatic analysis of the stationary phase expansion of the oscillatory integral. The algorithm is particularly effective for Euclidean plane domains possessing a ‫ޚ‬ 2 symmetry which reverses the orientation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 27 publications
3
72
0
Order By: Relevance
“…Some results similar to this, though for singularities of the wave trace at periodic orbits, can be found in [18,Section 5].…”
Section: 5supporting
confidence: 50%
See 2 more Smart Citations
“…Some results similar to this, though for singularities of the wave trace at periodic orbits, can be found in [18,Section 5].…”
Section: 5supporting
confidence: 50%
“…Thus, when ξ 2 < (1+h 2 )η 2 , there are solutions to (18) and (19) with initial condition a j (0, y, ξ, η) = 0, and we can find the Taylor expansions for a j at x = 0. Note that using a cut-off function to excise a conic neighborhood of η = 0 produces a smooth error, sinceΦ is rapidly decreasing there.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…If it were, then Siburg's results would imply that the marked length spectrum is preserved [Siburg 1999;2004]. In [Zelditch 2009; it is shown that analytic domains with one symmetry are spectrally determined if the length of the minimal bouncing ball orbit and one iterate is a -isospectral invariant. The prior results on -isospectral deformations that we are aware of are contained in the articles [Guillemin and Melrose 1979a;Popov and Topalov 2003; and concern deformations of boundary conditions.…”
Section: Hamid Hezari and Steve Zelditchmentioning
confidence: 99%
“…We give some extensions of this result to other planar waveguide settings in §7, to which we refer for specific statements. Theorem 1.1 bears some resemblance to results of Zelditch [9,10,11] on recovering planar domains with one symmetry from the spectrum of the Laplacian. Zelditch's proof uses the study of singularities of the fundamental solution of the wave equation which propagate along a single isolated periodic broken geodesic.…”
Section: Introductionmentioning
confidence: 53%